Humans Are Not Machines: The Behavioral Impact of Queueing Design on Service Time - Shunko, Masha; Niederhoff, Julie; Rosokha, Yaroslav (Management Science, 2018)
Using behavioral experiments, we study the impact of queue design on worker productivity in service systems that involve human servers. Specifically, we consider two queue design features: queue structure, which can be either parallel queues (multiple queues with a dedicated server per queue) or a single queue (a pooled queue served by multiple servers), and queue-length visibility, which can provide either full or blocked visibility. We find that (1) the single-queue structure slows down the servers, illustrating a drawback of pooling, and (2) poor visibility of the queue length slows down the servers; however, this effect may be mitigated, or even reversed, by pay schemes that incentivize the servers for fast performance. We provide additional managerial insights by isolating two behavioral drivers behind these results—task interdependence and saliency of feedback. Data are available at https://doi.org/10.1287/mnsc.2016.2610 . This paper was accepted by Gad Allon, operations management.